TINJAUAN FILSAFAT KESEMESTAAN BAHASA TERHADAP ANALISIS KONTRASTIF DAN PENERAPANNYA DALAM PEMBELAJARAN BAHASA ARAB - Enjang Burhanudin Yusuf (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2016)
Every language has its own structure and feature. Structure has language patterns that form their own feature and uniqueness. Language universality theory sees that all languages in this world have their own uniqueness as well as similar feature or characteristic for all languages. The different and similar character is studied by contrastive analysis so that students’ language mistakes can be predicted. In turn, the mistakes that caused by mother tongue usage influence can be fixed. The analysis result is used to accomplished students language skill. Furthermore, the aim is to help students to realize language mistakes so that students can master their learned language in shorter time. The contrastive analysis focuses on surface language such as phonology, morphology, and syntax because language is easily compared in this area. By mastering this knowledge, teacher will hold learning that emphasizes on differences between those two languages rather than the similarities.